Ecological Kufr in Modern Era: A Thematic Interpretation and Its Enviromental Implications - Nurfadilah, Aninda; Yeda Sahaya, Yeda Sahaya; Hakim, Lukmanul; Saifullah; Raffin Althafullayya, Muhammad (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
The increasingly worrying ecological crisis demands a re-reflection of spiritual values and environmental ethics in Islam. The Qur'an teaches the principle of balance (mizan) and man's responsibility as a caliph in managing nature. This study seeks to analyze the concept of ecological kufr in the Qur'an through the study of several verses that mention environmental damage (fasad fi al-ard) and denial of Allah's favor. The analysis was carried out by examining the meaning of the verse contextually and intertextually through an approach of interpretation and ecotheological reflection. The study results show that destructive behavior towards nature is a tangible form of theological denial, which brings moral and spiritual consequences to human life. This research confirms the importance of revitalizing revelation-based environmental ethics to answer modern ecological challenges. Thus, the Qur'an can be a normative foundation for building environmental awareness and sustainable conservation strategies.